Habitat selection and use by sympatric, translocated greater sage‐grouse and Columbian sharp‐tailed grouse. Issue 8 (18th September 2015) - Stonehouse, Kourtney F.; Shipley, Lisa A.; Lowe, Jason; Atamian, Michael T.; Swanson, Mark E.; Schroeder, Michael A.
ABSTRACT Greater sage‐grouse (Centrocercus urophasianus) and Columbian sharp‐tailed grouse (Tympanuchus phasianellus columbianus) have declined substantially in Washington, USA, primarily because native shrub‐steppe has been converted to agriculture. In response, state and federal agencies have acquired and restored habitat, and augmented and reintroduced grouse to suitable areas. We examined how sympatric, translocated sage‐grouse and sharp‐tailed grouse used space and selected habitats within their spring–summer home ranges and at nest sites within remnant shrub‐steppe surrounded by a matrix of cropland in eastern Washington. Because their life‐history requirements differ, we expected extensive habitat partitioning between species. Using radiolocations of ≥43 birds of each species, we found that sage‐grouse had larger spring–summer home ranges than sharp‐tailed grouse, and the composite of home ranges for sharp‐tailed grouse fell almost completely within the composite of home ranges for sage‐grouse. By creating resource utilization function models using radiolocations of ≥53 birds of each species, we found that areas of highest predicted intensity of use for both species overlapped by >50%, even at the top 5% quantile. Both species used restored fields and areas farther from trees and roads or distribution lines more intensely. Sage‐grouse used less rugged areas more intensely, and both species used 3 levels of shrub cover equally. To compare selection of nest sites relative to available sites for nesting in both species, we created resource selection function models for ≥30 birds of each species and found that sage‐grouse selected areas farther from distribution lines, whereas sharp‐tailed grouse selected restored fields. When we examined vegetation characteristics used by female sage‐grouse and sharp‐tailed grouse at nest sites using a case‐control, use versus non‐use design for ≥26 birds of each species, we found sage‐grouse used areas with greater shrub cover, lower annual forb cover, and taller perennial grasses, whereas sharp‐tailed grouse used areas with greater perennial grass cover and taller perennial grasses and forbs. When we compared habitat features measured at nest sites between species, we found sage‐grouse used areas with greater moderate and dense shrub cover, lower sparse shrub cover, less restored fields, higher patch diversity, and areas farther from distribution lines than sharp‐tailed grouse. These differences resulted in only 38% overlap of areas within the top quartile of relative selection values for nest sites by the 2 species, and <10% at the top 5% quantile. Because many western states are highly fragmented by cropland, understanding how populations of species with different life‐history characteristics, such as sage‐grouse and sharp‐tailed grouse, coexist within remaining tracts of shrub‐steppe at different spatial scales is important for effectively conserving and managing shrub‐steppe communities. © 2015 The Wildlife Society.